The Effect of Microelements on Tobacco Activity - Hashimov F. X; Karimova Kh.B. (Indonesian Journal of Innovation Studies, 2019)
The article contains some information on the specific effects of molybdenum, cobalt and copper cellulose in the "Virginia" type "K-326" tobacco plant.